Bildrik populärvetenskap om dansk-judisk historia - Carlsson, Carl Henrik (Nordisk judaistik/Scandinavian Jewish Studies, 2018)
Recension av Cecilie Felicia Stokholm Banke, Signe Bergman Larsen, Janne Laursen, Martin Schwarz Lausten, Hanne Trautner-Kromann, En indvandringshistorie. Jøder i Danmark 400 år (Dansk Jødisk Museum 2018). Engelsk version: A Story of Immigration. Four Hundred Years of Jews in Denmark. Translation: Virginia Laursen and Fran Hopenwasser (The Danish Jewish Museum 2018).